Peningkatan Hasil Belajar Mengoperasikan Sistem Pengendali Elektromagnetik Siswa dengan Media Pembelajaran Berbasis Festo Fluidsim - Andre Gustian; Fivia Eliza (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
This research is motivated by the teacher who only explains the material to be practiced verbally, and the series of pictures that will be practiced are illustrated by the teacher on the board, and the teacher directly instructs students to do the practice. This makes it difficult for students to understand and analyze the working principles of the control system, and so far students are only able to assemble and operate the circuit but students have not been able to explain how the circuit can operate. Therefore we need learning media that can support this, one of them is by applying Festo Fluidsim simulation learning media. This type of research is a descriptive study with quasi-experimental methods with the design of One Group Post-test Only. From the results of the study obtained an average post-test score of 76.63. With the t test analysis obtained t count = 2.754 which is greater than the table = 2.492 at the 0.01 significance level. Thus it can be concluded that there is an increase in student learning outcomes after the application of simulation software in the learning process of MSPEM class XI TITL SMKN1 Tilatang kamang.